2018
DOI: 10.1002/jcsm.12305
|View full text |Cite
|
Sign up to set email alerts
|

The deterioration of muscle mass and radiodensity is prognostic of poor survival in stage I–III colorectal cancer: a population‐based cohort study (C‐SCANS)

Abstract: BackgroundMuscle abnormalities such as low muscle mass and low muscle radiodensity are well known risk factors for unfavourable cancer prognosis. However, little is known in regard to the degree and impact of longitudinal changes in muscle mass and radiodensity within the context of cancer. Here, we explore the relationship between muscle wasting and mortality in a large population‐based study of patients with non‐metastatic colorectal cancer (CRC).MethodsA total of 1924 patients with stage I–III CRC who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
90
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 36 publications
1
90
1
Order By: Relevance
“…Regarding the prognostic value of skeletal muscle radiodensity (SMD), only one study by Sjoblom et al . showed that SMD had a statistically significant negative prognostic value in non‐small cell lung cancer (NSCLC) patients, 15 a finding also reported in other types of tumors …”
Section: Introductionmentioning
confidence: 57%
“…Regarding the prognostic value of skeletal muscle radiodensity (SMD), only one study by Sjoblom et al . showed that SMD had a statistically significant negative prognostic value in non‐small cell lung cancer (NSCLC) patients, 15 a finding also reported in other types of tumors …”
Section: Introductionmentioning
confidence: 57%
“…Evaluating muscle at a single specific time point may not help in predicting survival and could not evaluate muscle loss . These findings suggested that a longitudinal study of changes in body composition may provide a more comprehensive understanding of the impacts of body composition on outcomes …”
Section: Discussionmentioning
confidence: 99%
“…49,62 These findings suggested that a longitudinal study of changes in body composition may provide a more comprehensive understanding of the impacts of body composition on outcomes. [40][41][42][43][44][45][46][47][48][49] Body mass index is an imprecise measure of body composition, and monitoring BMI changes may be insufficient to promptly identify occult body composition changes. 18,19 We found that changes in SMI and TATI were weakly correlated with the change in BMI, and changes in SMD and SMG showed no correlation with the BMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is its small sample size and the retrospective design. In addition, we were not able to measure the skeletal muscle density, which has been reported to be a useful prognostic factor in patients with various cancer types [21,22].…”
Section: Discussionmentioning
confidence: 92%